Protein Engineering of Candida antarctica Lipase A : Enhancing Enzyme Properties by Evolutionary and Semi-Rational Methods - Sandström, Anders G. (Stockholms universitet, Institutionen för organisk kemi, 2010)
Enzymes are gaining increasing importance as catalysts for selective transformations in organic synthetic chemistry. The engineering and design of enzymes is a developing, growing research field that is employed in biocatalysis. In the present thesis, combinatorial protein engineering methods are applied for the development of Candida antarctica lipase A (CALA) variants with broader substrate scope and increased enantioselectivity. Initially, the structure of CALA was deduced by manual modelling and later the structure was established by X-ray crystallography. The elucidation of the structure of CALA revealed several biocatalytically interesting features. With the knowledge derived from the enzyme structure, enzyme variants were produced via iterative saturation mutagenesis (ISM), a powerful protein engineering approach. Several of these variants were highly active and enantioselective towards bulky esters. Furthermore, an extensively combinatorial protein engineering approach was developed and investigated. A CALA variant with a spacious substrate binding pocket that can accommodate an unusually bulky substrate, an ester derivate of the non-steroidal anti-inflammatory drug (S)-ibuprofen, was obtained with this approach. === At the time of the doctoral defence the following paper was unpublished and had a status as follows: Paper nr. 5: Manuscript